The Nusantara model of Islam: a counter discourse of Islamic state in Southeast Asia - Mundayat, Aris Arif (Institute of Islam Hadhari, Universiti Kebangsaan Malaysia; together with Faculty of Human Ecology, Universiti Putra Malaysia; and Department of Islamic Development Malaysia, 2015)
The impact of conflict in Iraq and Syria has stimulated the idea of Islamic State (IS) in Southeast Asia, even the governments in this region have become worried by the potential threat of Islamic State. The recruitment of the jihadist from Southeast Asia to involve in Syrian civil war predicted as high as 1000 people. The social media has facilitated the recruitment process of the jihadist from Southeast Asia to Iraq and Syria. As the governments in the region are facing the spectre of renewed terrorism inspired by trans-national terrorist group by using counter terrorist security approach would only create never ending fire with fire, how is the alternative response at the community level need to be developed as cultural approach. The alternative model that will be examined in this paper is “How is the potency of Nusantara Model of Islam as counter discourse against the Islamic State model of Iraq and Syria”. This paper will discuss the mode of Islamization in Southeast Asia which is based on the cultural approaches historically. Then continue with the discussion of the emerging strategy such as “cultural Islam”, “civic Islam”, “political Islam” and khilafah whih is categorised as “radical political Islam”. The cultural Islam, civic Islam and political Islam are using cultural, civic, and democratic approach; meanwhile the radical political Islam is refusing democracy and considers cultural approach as against the Islamic teaching. The “Nusantara model of Islam” is within the range of cultural, civic, and political Islam that believe in peaceful process of Islamization. This model needs to be examined within the context of ASEAN Cultural Community 2015.